Treatment Non-Compliance in Bipolar Affective Disorder Patients: A Study from a Tertiary Care Centre in Nepal - Subedi, Sandip; Paudel, Kamala (Journal of Karnali Academy of Health Sciences, 2020)
Background: Treatment Non-compliance is a major challenge in the treatment of Bipolar Affective Disorder as it can give rise to lots of unwanted consequences. Therefore, understanding various reasons for non-compliance and taking steps to reduce it is a key step in minimizing the unwanted consequences. Thus, This study was done to identify the pattern of non-compliance in patients with Bipolar Affective Disorder. Methods: This was a cross-sectional study including 76 patients who attended Psychiatry OPD of Universal College of Medical Sciences. Socio-demographic datasheet, Datasheet for various factors related to non-compliance, Morisky 8-Item Medication Adherence Scale (MMAS-8) and Descriptive summaries of socio-demographic and contributing factors for all patients were used to record the data. Results: Out of a total of 76 patients, males (55.2%) were slightly higher than Females. The mean age of participants was 35.78±12.25 years. About 76.8% of the patients were non-compliant. High non-compliance was seen in age below 40 years (48.7%), male (52.6%) and duration of illness up to 15 years (78.9%), having up to 3 pills (44.7%) and having previous treatment history (60.5%). Conclusion: Treatment non-compliance was very high in patients with BPAD. Appropriate measures need to be taken care of to reduce non-compliance.